Persepsi petani terhadap introduksi budidaya tomat (Lycopersicum esculentum) di Desa Kumpai Batu Atas Kabupaten Kotawaringin Barat - Juliandi, Dwi; Selvia, Jerry; Djoni, Djoni (Agrokompleks, 2025)
West Kotawaringin Regency is one of the largest tomato-producing areas in Central Kalimantan, contributing significantly to the region’s tomato harvest. In the Arut Selatan District area, particularly in Kumpai Batu Atas Village, tomato plants have great potential to increase productivity, as there is still a significant amount of ample land that can be utilized. To increase productivity, the TPHP Service is implementing one of its programs, namely the introduction of tomato plants in Kumpai Batu Atas Village. This research aims to determine the level of productivity in tomato farming and farmers’ perceptions of the tomato cultivation introduction program in Kumpai Batu Atas Village, implemented by the Horticulture and Plantation Food Crops Service of West Kotawaringin Regency. The data analysis method used is a descriptive, quantitative approach with a Likert Scale. The research results indicate that the average productivity of tomato farming in Kumpai Batu Atas Village is 5.3985 kg/ha, with an average harvest area of 0.54 ha and a total production of 2,927 kg per planting season. Farmers’ perceptions of the introduction of tomato cultivation by the Horticulture and Plantation Food Crops Service are perfect, seen from the cognitive aspect with a percentage of 88%, the affective element at 88.5%, and the conative aspect at 88% with the overall perception being in the very agree/excellent perception category. with an interpretation percentage of 88%.